Linguocultural Analysis of Gothic Lexemes and Female Identity in Dahshat and the Yellow Wallpaper: A Cross-Cultural Study Toward Sustainable Development Goals (SDGs) - Makhmudov, Kudratbek; Khodjamkulov, Umid; Saitkulova, Nazokat; Khaldarchaeva, Gaukhar; Baisov, Akhmad; Babadjanova, Nargiza (International Journal of Language Education, 2025)
This study aims to analyze gothic lexemes in Abdulla Qahhor’s Dahshat and Charlotte Perkins Gilman’s The Yellow Wallpaper to understand how language reflects fear, identity, and cultural repression. Using qualitative textual analysis, the study explored semantic fields related to death, madness, and female agency within two contrasting cultural contexts. The analysis revealed that Dahshat employs external folkloric lexicon rooted in oral tradition and religious rites, while The Yellow Wallpaper uses symbolic language to depict internalized psychological horror. These differences emerge because each text mirrors culturally specific models of fear—socialized and communal in Uzbek society, individual and medicalized in 19th-century America. The research contributes to language and literature education by promoting critical awareness of culture and gender in text analysis, supporting Sustainable Development Goals (SDG 4 and 5). The findings offer pedagogical applications in linguocultural literacy, encouraging transdisciplinary teaching in literature, gender studies, and cross-cultural communication.